2021
DOI: 10.1101/2021.02.08.21250899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinatorial analysis of phenotypic and clinical risk factors associated with hospitalized COVID-19 patients

Abstract: Characterization of the risk factors associated with variability in the clinical outcomes of COVID-19 is important. Our previous study using genomic data identified a potential role of calcium and lipid homeostasis in severe COVID-19. This study aimed to identify similar combinations of features (disease signatures) associated with severe disease in a separate patient population with purely clinical and phenotypic data. The PrecisionLife combinatorial analytics platform was used to analyze features derived fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
2
1
Order By: Relevance
“…In our monocentric study, first we observed that 44.8% of our hospitalized COVID-19 patients had low serum and ionized calcium level, corrected to the concentration of albumin. This percentage is not as high as those reported in other studies [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ], but the results are nonetheless relevant considering that the recorded calcium value interquartile range is from 8.3 to 9 mg/dL for serum calcium (reference range 8.5 to 10.5 mg/dL) and from 1.05 to 1.16 mmol/L for ionized calcium (reference range 1.1 to 1.3 mmol/L), shifting the population curve towards the lower limit and without any case of hypercalcemia. Indeed, the average value of both parameters highlights the prevalent condition of hypocalcemia (calcium level especially ≤8.5 mg/dL).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In our monocentric study, first we observed that 44.8% of our hospitalized COVID-19 patients had low serum and ionized calcium level, corrected to the concentration of albumin. This percentage is not as high as those reported in other studies [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ], but the results are nonetheless relevant considering that the recorded calcium value interquartile range is from 8.3 to 9 mg/dL for serum calcium (reference range 8.5 to 10.5 mg/dL) and from 1.05 to 1.16 mmol/L for ionized calcium (reference range 1.1 to 1.3 mmol/L), shifting the population curve towards the lower limit and without any case of hypercalcemia. Indeed, the average value of both parameters highlights the prevalent condition of hypocalcemia (calcium level especially ≤8.5 mg/dL).…”
Section: Discussioncontrasting
confidence: 53%
“…Several biochemical parameters have been evaluated and particular attention has been focused on calcemia, also considering the primary role of calcium for viral infection and replication [ 9 ]. Particularly, it has been reported that a high percentage of COVID-19 hospitalized patients showed hypocalcemia [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ], a condition that can be critical, especially for patients with pre-existing chronic pathologies [ [20] , [21] , [22] , [23] ]. Our retrospective analysis also confirms that serum calcium concentration is the most altered parameters among hospitalized COVID-19 patients, especially in those with the most critical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The combinatorial approach is more sensitive than GWAS, enabling identification of novel genetic associations and mechanisms that may only be relevant to a subgroup of patients, leading to more validated associations than GWAS when analyzing the same datasets. This approach has been validated in multiple disease studies both by the authors and collaborators, in some cases using in vitro and in vivo disease assays to demonstrate novel target genes' disease modification potential, and in others by the presence in pharmaceutical companies' R&D pipelines of drug programs targeting mechanisms that were identified by combinatorial analysis, but which could not be found using GWAS on available patient datasets 16,17,18 .…”
Section: Combinatorial Analysismentioning
confidence: 99%